A case of T1 multiple lower jaw gingival squamous cell carcinoma cases that progressed to the parapharyngeal space - Toru Inomata; Jumpei Tanaka; Naruhisa Tanaka; Saki Tanno; Toshimasa Machida; Masao Kurosaka; Chihiro Fushimi (Elsevier, 2022)
Parapharyngeal space infiltraion by head and neck carcinoma is often reported. However, most of them are advanced primary cancer and early cancer case is very rare. we reported a case of cT1 squamous cell carcinoma of the gingiva that arise multiple metachronous mucosal lesions, cervical; metastases and finally parapharyngeal space involvement. The patient was 78-year-old female who visited our hospital with chief complaint of white lesion in the gingiva. A slightly protruded mass, 16mm in size, was founded on the left mandibular buccal gingiva of canines. The mass was excised by tumorectomy with clinical diagnosis as non-malignant lesion and histopathological diagnosis was squamous cell carcinoma. Seven months after the removal of the primary cancer, mucosal change was observed adjacent to primary cancer site and marginal mandibulotomy was performed with clinical diagnosis as cancer recurrence. Third lesion clinically occurred as granulomatous lesion in the posterior part of the last operation site. Remarginal mandibulotomy was performed under the clinical diagnosis of the cancer recurrence. Then aberrant swelling of the left neck lymph node was clinically observed and radical neck dissection was conducted under the clinical diagnosis of primary cancer metastasis. Histologically, extranodal extension spread was observed in Level IB and IIA. adjuvant chemo-radiation therapy was conducted and was completely done without any adverse reaction. However, tumor infiltrate to the parapharyngeal space was observed by the radiological inspection and then patient was died.